Advances in temporomandibular joint reconstruction in TMJ ankylosis : Our experiences and literature review - Passi, Deepak; Singh, Geeta; Singh, Satyavrat; Mehta, Gagan; Dutta, Shubha Ranjan; Sharma, Sarang (International Journal of Dental Research, 2014)
The treatment of temporomandibular joint ankylosis poses a significant challenge because of the high incidence of recurrence .The only treatment option for TMJ ankylosis is surgical with or without condylar reconstruction. Various grafts are available for condylar reconstruction after removing  the ankylotic mass such as costochondral, sternoclavicular, posterior border of mandibular ramus, fibular, coronoid process, and metatarsophalangeal, alloplastic graft like hydroxyappatite collagen and recently condylar distraction osteogenesis. To date, there is no ideal autogenous graft for condylar reconstruction that satisfies the complex anatomy and the myriad of functions of a missing condyle. This study was conducted to determine the efficacy of using the various autogeneous and alloplastic graft and condylar distraction osteogenesis for reconstruction of mandibular condyle. Keywords: TMJ (Temporomandibular Joint); CCG (Costochondral Graft); SCG (Sternoclavicular Graft); DO (Distraction Osteogenesis).